Analisis Teknik Identifikasi Karakteristik untuk Materi pada Tema Pengalamanku di Kelas 1 SD Negeri 15 Tangerang - Magdalena, Ina; Sefani, Nur Aliza; Nuraeni, Eni (YASIN, 2023)
In understanding the characteristics of each student, it is actually heterogeneous. In this case it can be seen that not all students can participate in learning activities easily. Identification of the character of students actually requires a juridical basis and a theory. the researcher provides an understanding with the aim of identifying the character of students in class 1 at SD Negeri 15 Tangerang through techniques adapted to educators. In this study using qualitative methods and support from data collection through observation, interviews and also documentation to support the data from this study. The results of the study show that in fact the characteristics identification technique for students actually requires conformity developed by educators to be able to provide more attractiveness and adaptation to children. These techniques include self-mastery techniques, class mastery, material mastery, approaches to students and also language delivery events or even the way teachers dress. This is actually an important element in identifying the character of students.